Application of Blended Learning to Enhance 21st Century of Student Learning - Merrisa Monoarfa; Mardia Bin Smith; Sukma Nurilawati Botutihe (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The rapid development of technology today can support Blended learning as a form of learning process in increasing student learning motivation in this century, this learning innovation is expected to aim as an increase in student learning motivation accompanied by strategic steps of educators to increase student motivation. This study aims to analyze the Blended Learning method of student learning motivation in the 21st century. The data collection method is carried out by literature study or library method, focusing on Blended Learning related to learning motivation in 21st Century Education. This study shows that Blended Learning can answer problems by increasing student learning motivation by paying attention and combining online and ofine learning. Thus, it can be concluded that the use of blended learning methods is effective because it makes the learning process more exible, supported by the development of technology, information, and communication, so that it can increase the motivation and independence of students in the 21st century.